(untitled) (LEARNing Landscapes, 2013)
As online education providers gain a foothold in the US public education system nationwide as supplemental and primary providers of curriculum materials, they are replicating some of the same pedagogical mistakes that brick-and-mortar schools have created in the curriculum development process—by not accommodating the struggling learner. Our paper and discussion concerns K-12 online content providers and their curriculum development processes.